ANALYSIS OF AIRBORNE MICROPLASTICS IN SCHOOL INDOOR ENVIRONMENTS IN JEMBER REGENCY - Cantika Almas Fildzah; Yogy Nur Fadillah; Abdur Rohman; Farid Zulfa Fakhruddin (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2026)
Plastic can degrade into smaller particles ranging from 1 μm to 5 mm, known as microplastics. Due to their small size, microplastics can be easily inhaled and enter the human respiratory system. The high respiratory rate and underdeveloped immune systems of children make them more vulnerable to exposure to airborne microplastics. This study aimed to determine the characteristics and abundance of airborne microplastics in school indoor environments in urban areas of Jember Regency. The study was conducted in four schools representing different educational levels, namely kindergartens and junior high schools, selected using stratified random sampling. Sampling was carried out using a passive sampling method by placing stainless-steel boxes at a height of 1.2 m for 24 hours. Sample pre-treatment included filtration using 1.2 μm filter paper, density separation using ZnCl₂ (1.6 g/cm³), and organic matter digestion using 30% H₂O₂. Microplastic abundance and characteristics were then analyzed using microscopy and Fourier Transform Infrared Spectroscopy (FTIR). The highest microplastic density was found in Kindergarten A, reaching 2,239 particles/m²/day, followed by Junior High School C (1,143 particles/m²/day), Junior High School D (1,109 particles/m²/day), and Kindergarten B (603 particles/m²/day). Fiber-shaped microplastics were the dominant form, followed by fragments. Black-colored particles with sizes ranging from 0.2 to 2 mm were most frequently observed, polyethylene terephthalate (PET) and Polyvinyl Alcohol (PVA) were identified in the sample.